(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This article provides a comprehensive overview of asset pricing models, which are widely used in finance to determine the appropriate prices and expected returns of various financial assets. Starting with the foundational concepts of risk and return, the article delves into different asset pricing models, including the Capital Asset Pricing Model (CAPM), Arbitrage Pricing Theory (APT), and the Fama-French Three-Factor Model. Each model’s key assumptions, formulation, and practical applications are discussed, highlighting their strengths and limitations. Furthermore, the article explores more recent developments in asset pricing models, such as the consumptionbased models and the factor-based models. By gaining a deeper understanding of asset pricing models, investors and financial professionals can make more informed investment decisions and assess the pricing efficiency of financial markets.